The Relationship Between The Duration Of Gadget Use And Sitting Position To The Risk Of Low Back Pain (Lbp) Incidence In Students In Bogor: Hubungan antara Durasi Penggunaan Gadget dan Posisi Duduk dengan Risiko Kejadian Nyeri Punggung Bawah (LBP) pada Mahasiswa di Bogor - Sari Dwi Tofani; Muhammad Didin Wahyudin; Pipit Pitriani; Suryadi; Osty Histry Kapahang; Yanna Dwi Saptarani (Journal of Nursing Education and Practice, 2026)
Introduction: Low back pain in adolescents is a serious health problem that is receiving increasing attention worldwide. The condition is quite common, with approximately 46.7% in 15-year-olds. This problem not only affects the physical body, but can also interfere with daily activities, including school activities, sports, and sleep quality. If not managed properly, adolescent LBP has the potential to develop into a chronic condition in adulthood. Objective: to analyze the relationship between the duration of gadget use and sitting position on the incidence of low back pain in students of SMAN 1 Parung, Bogor Regency. Method: a quantitative design with a cross-sectional approach was used. This study was conducted on January 23, 2025 with a sample of 267 students selected using a stratified random sampling technique. Results: univariate analysis of frequency distribution was performed. Bivariate analysis using the Spearman Rank (Rho) test found no significant relationship between the duration of gadget use and the incidence of LBP, with a p-value of 0.505 > 0.05. The analysis of the relationship between sitting position and the incidence of LBP found a relationship with a coefficient value of -0.174 and a p-value of 0.004 < 0.05. Conclusion: It was found that there is no relationship between the duration of gadget use and the incidence of low back pain in students of SMAN 1 Parung, Bogor Regency, with a p-value of 0.505 > 0.05. It was found that there is a relationship between sitting position and the incidence of low back pain among students of SMAN 1 Parung, Bogor Regency, with a p-value of 0.004 < 0.05.